In vitro and in vivo assessments of Artemisia argyi fermented with Lactobacillus plantarum WLPL01 as an alternative anti-Salmonella agent. (August 2021) - Tao, Xueying; Tian, Linlin; Zhan, Hui; He, Yao; Zhong, Changcheng; Wei, Hua
Abstract: Immediate attention has been drawn to the discovery of anti-infection strategies to avoid rapid development of antibiotic resistance in pathogens. Our prior study has demonstrated that probiotic Lactobacillus plantarum WLPL01-fermented Artemisia argyi liquid broth could inhibit the growth of Listeria monocytogenes CMCC54007 and Candida albicans ATCC14053. In this study antagonistic effect of Artemisia argyi fermentation liquid (AAFL) on Salmonella Typhimurium ATCC13311 was systematically evaluated by culture inhibition assay in vitro, adhesion and invasion assays using HT-29 cell line, and measurements of epithelial barrier integrity and cytokines in mice. Results showed that AAFL (50, 25 and 15 mg/mL) significantly inhibited the growth of S. Typhimurium ATCC13311 in vitro ( P  < 0.05); 5 mg/mL of AAFL achieved maximal reduction of adhesion and invasion rate by 41.92% and 24.03%, respectively, and down-regulated sipA by 5.26 folds in HT-29 cell line. Anti-infection experiment in mice showed that 25 mg/mL of AAFL significantly ( P  < 0.05) decreased the load of S. Typhimurium ATCC13311 in gastrointestinal tract (ileum, colon and cecum) and internal organs (liver, spleen and MLN), improved epithelial barrier integrity, and decreased physiological score as well as the levels of pro-inflammation cytokines in the serum. In conclusion, AAFL might be a potential probiotic fermentation liquid against S. Typhimurium infection. Highlights: Artemisia arygi was fermented by native lactobacilli for the first time. First assessment of anti-infection of AAFL prepared by native lactobacilli. First exploration of anti- Salmonella mechanism of AAFL prepared by native lactobacilli.